The co-construction of a collective memory: compensation and repentance at the heart of a discursive conflict concerning Algerian-French history - Rai , Aicha; Immoune , Youcef (El Omda in Linguistics and Discourse Analysis, 2023)
This study focuses on the use of lexical items (history/memory, compensation/repentance) by political discourse actors within a conflictual context, particularly that of Algerian-French relations. It is based on a logometric and pragmatic analysis of a corpus made up of more than forty official French and Algerian political speeches addressing bilateral relations and shared history. These official speeches are also compared with more than forty press articles from both countries dealing with the same topic. This approach enables a clearer understanding of the circulation of these lexical items within this discursive space (2007–2016)